2020
DOI: 10.1177/0363546520969883
|View full text |Cite
|
Sign up to set email alerts
|

The Clinically Important Difference and Patient Acceptable Symptomatic State for Commonly Used Patient-Reported Outcomes After Knee Cartilage Repair

Abstract: Background: In patients undergoing cartilage restoration of the knee, limited information is available regarding clinically important difference (CID) and Patient Acceptable Symptomatic State (PASS) estimates for commonly used patient-reported outcome measures (PROMs). Purpose: The objective of this study was to determine the CID and PASS in the population with knee cartilage restoration for the Knee injury and Osteoarthritis Outcome Score (KOOS), the International Knee Documentation Committee Subjective Knee … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 18 publications
1
38
1
Order By: Relevance
“…The KOOS Symptom subscale was not used due to lack of reliability in UKA patients [22]. The PASS threshold value for the Lysholm score is reported as 70 [2].…”
Section: Clinical Assessment With Patient Acceptable Symptom State/ O...mentioning
confidence: 99%
See 1 more Smart Citation
“…The KOOS Symptom subscale was not used due to lack of reliability in UKA patients [22]. The PASS threshold value for the Lysholm score is reported as 70 [2].…”
Section: Clinical Assessment With Patient Acceptable Symptom State/ O...mentioning
confidence: 99%
“…P-value for comparisons of proportions of patients meeting PASS between ACL-deficient and ACL-intact groups. b PASS was defined as KOOS Pain ¼ 87; KOOS ADL ¼ 87.5; KOOS Sport ¼ 43.8; KOOS Quality of Life ¼ 66[3]; Lysholm ¼ 70.3[2].…”
mentioning
confidence: 99%
“…T H E J O U R N A L O F B O N E & JOINT SURGERY d J B J S . O R G VOLUME 104-A d NUMBER 18 d S E P T E M B E R21, 2022 …”
mentioning
confidence: 99%
“… 6 However, for patients who had undergone cartilage restoration procedures, the PASS threshold of the IKDC-SKF was 62.1. 4 The current study found that the PASS threshold of the Thai version of the IKDC-SKF for patients with ACLR was marginally lower than that of the original IKDC-SKF (74.2 vs 75.9, respectively). 15 With a cutoff of 75.9, the sensitivity decreased from 0.72 to 0.67, but the specificity was maintained at 0.82.…”
Section: Discussionmentioning
confidence: 50%